MEASURES AIMED AT PROMOTING TOURIST DESTINATIONS OF THE RUSSIAN FEDERATION ABROAD - Pogrebova, Elena; Allanina, Liliya; Yakhyaeva, Marhat; Bekirova, Sevil; Stepanova, Diana (Revista Inclusiones, 2020)
The development of inbound tourism is one of the important tasks of the formation of a basis for sustainable economic growth and an effective way to increase the share of non-oil exports in the total exports of the Russian Federation. Tourism provides an inflow of funds into the country's economy and has a powerful synergistic effect. It stimulates the increase of incomes of 53 sectors of the national economy involved in the creation of tourism products and is a multiplier of employment and self-employment, promoting the development and involvement in the export activities of small and medium-sized businesses, improving the living conditions of the local population and smoothing the imbalances of territorial development.